Method for in-situ blending modification of phthalonitrile resin by using polydopamine nano-microspheres, composite material prepared by using method and application of composite material

By depositing polydopamine nanospheres on the surface of carbon fiber fabric, in-situ blending modification of phthalonitrile resin is achieved, and a continuous three-dimensional cross-linked network is constructed. This solves the problem of uneven dispersion of phthalonitrile resin in traditional modification methods, improves the high-temperature mechanical properties and thermal stability of the composite material, and makes it suitable for aerospace and high-temperature structural components.

CN121006068APending Publication Date: 2025-11-25HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511089455.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-05
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Phthalocyanine resins are difficult to disperse uniformly and react synergistically using traditional modification methods, resulting in internal stress concentration, uneven curing, and structural defects, which limits their application in engineering structural composite materials.

Method used

A method for in-situ blending and modifying phthalonitrile resin with polydopamine nanospheres was adopted. By depositing polydopamine nanospheres on the surface of carbon fiber fabric, the functional groups of polydopamine nanospheres were used to induce a high-temperature blending reaction of phthalonitrile resin, thereby constructing a continuous three-dimensional cross-linked network, achieving uniform dispersion of the material and improving its high-temperature mechanical properties.

Benefits of technology

After thermal aging at 400°C, the prepared composite material exhibits a shear strength of no less than 50% of its initial value and a flexural strength of no less than 60%, significantly improving its high-temperature mechanical load-bearing capacity and thermal stability, making it suitable for aerospace and high-temperature structural components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121006068A_ABST
    Figure CN121006068A_ABST
Patent Text Reader

Abstract

The invention discloses a method for modifying phthalonitrile resin through in-situ blending of polydopamine nano-microspheres, a composite material prepared by the method and application of the composite material, and belongs to the technical field of processing of high-performance polymer materials and composite systems of the high-performance polymer materials. The problems that existing phthalonitrile resin is difficult to blend and modify uniformly, the mechanical property is limited and the like are solved. A uniformly deposited polydopamine nano structure is constructed on the surface of a carbon fiber fabric, functional groups such as phenolic hydroxyl groups and amino groups in polydopamine microspheres are utilized to induce phthalonitrile resin to be subjected to an in-situ blending reaction with the carbon fiber fabric at a high temperature, and a three-dimensional reaction area with fiber-polydopamine microsphere-phthalonitrile resin as a continuous path is constructed; a cross-linked network which is compact in structure, continuous in bonding and three-dimensional synergistic is formed, so that the high-temperature mechanical bearing capacity and the high-temperature thermal exposure residual performance of the obtained composite material are remarkably improved while the excellent thermal stability of the composite material is maintained, and the composite material is suitable for the fields of aerospace, high-temperature structural parts and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for in-situ blending and modifying phthalonitrile resin with polydopamine nanospheres, the composite materials prepared therefrom, and their applications, belonging to the field of high-performance polymer materials and their composite systems processing technology. Background Technology

[0002] Phthalocyanine resin, as a typical high-performance thermosetting polymer, is widely used in high-end fields such as aerospace, electronic packaging, and heat-resistant structural components due to its excellent thermal stability, low outgassing rate, and superior high-temperature mechanical properties. However, phthalocyanine resin itself has problems such as weak molecular polarity, high viscosity, narrow processing temperature window, and phase transformation during thermosetting. These problems make it difficult to achieve uniform dispersion and synergistic reaction in traditional modification methods such as physical blending and filler compounding. Consequently, it leads to internal stress concentration, uneven curing, and structural defects in the material, limiting its further application in engineering structural composite materials.

[0003] Current research focuses on enhancing phthalonitrile systems through chemical grafting, functionalized additives, or surface modification. However, these methods suffer from problems such as complex processes, poor dispersibility, and limited applicability. In particular, there is a lack of novel blending strategies that combine structural continuity, reaction efficiency, and high-temperature performance in the large-scale preparation of composite materials. Summary of the Invention

[0004] To address the problems of uneven blending and limited mechanical properties in existing phthalocyanine resin modification, this invention provides a method for in-situ blending and modifying phthalocyanine resin with polydopamine nanospheres, the resulting composite materials, and their applications.

[0005] The technical solution of this invention: One objective of this invention is to provide a method for in-situ blending and modifying phthalocyanine resin with polydopamine nanospheres, the method comprising the following steps: (1) Clean and dry the carbon fiber fabric for later use; (2) Add dopamine hydrochloride to Tris-HCl buffer to obtain a reaction solution. Immerse the cleaned carbon fiber fabric in the reaction solution at room temperature and let it stand to react, and obtain carbon fiber fabric with polydopamine nanospheres deposited on the surface. (3) The carbon fiber fabric with polydopamine nanospheres deposited on its surface is immersed in phthalic acrylonitrile resin solution, and a segmented heating method is used for immersion pretreatment. Finally, a hot pressing process is used for curing treatment to obtain polydopamine nanosphere in-situ blended modified phthalic acrylonitrile resin.

[0006] Further specifying, (1) the operation process is as follows: use a mixed solution of acetone and anhydrous ethanol for ultrasonic cleaning for 30 min, and dry in a vacuum environment.

[0007] Further specified, the pH value of the Tris-HCl buffer in (1) is 8.5.

[0008] Further specified, the concentration of dopamine hydrochloride in the reaction solution of (2) is 0.5–5.0 g / mol.

[0009] Further, the static reaction time in (2) is 12-72h.

[0010] Further specifying, (3) the concentration of phthalic acid resin solution is 60-80wt%, the solvent is acetone or / and methyl ethyl ketone; the phthalic acid resin is a self-catalytic trimer PN resin with active phthalic acid groups at the end.

[0011] Further specifying, (3) the immersion pretreatment process is: keep warm at 50-80°C for 30 min, then raise the temperature to 120-250°C and keep warm for 30 min.

[0012] Further specifying, the curing process in (3) is as follows: First, maintain the temperature at 0.2-2 MPa and 100-200°C for 1-4 hours; Then, keep warm at 4-6 MPa and 200-300°C for 1-5 hours; Finally, the material is kept at 4-6 MPa and 300-400°C for 1-5 hours, then cooled to room temperature at a rate of 3-5°C / min before demolding.

[0013] The second objective of this invention is to provide a polydopamine nanosphere in-situ blended modified phthalocyanine resin composite material prepared by the above method, specifically, after heat aging at 400°C for 1 hour, its shear strength is not less than 50% of the initial shear strength and its flexural strength is not less than 60% of the initial flexural strength.

[0014] The third objective of this invention is to provide an application of the above-mentioned polydopamine nanosphere in-situ blended modified phthalonitrile resin composite material, specifically for the preparation of heat-resistant structural components.

[0015] Beneficial effects: This invention constructs a uniformly deposited polydopamine nanostructure on the surface of carbon fiber fabric. Utilizing the phenolic hydroxyl and amino groups in the polydopamine microspheres, an in-situ blending reaction is induced with phthalocyanine resin at high temperature, constructing a three-dimensional reaction zone with a continuous pathway of fiber-polydopamine microsphere-phthalocyanine resin. This results in a dense, continuously bonded, and three-dimensionally synergistic cross-linked network. By adjusting the particle size and density of the polydopamine microspheres, precise control over the blending behavior and network density of the phthalocyanine resin and polydopamine nanospheres is achieved. The resulting composite material maintains excellent thermal stability while significantly improving its high-temperature mechanical load-bearing capacity and residual performance after high-temperature heat exposure, making it suitable for aerospace, high-temperature structural components, and other fields. Experimental results show that after 1 hour of heat aging at 400°C, the shear strength of the obtained composite material is not less than 50% of the initial shear strength, and the flexural strength is not less than 60% of the initial flexural strength. Attached Figure Description

[0016] Figure 1 A photograph of the in-situ blended polydopamine nanospheres with phthalonitrile resin composite material prepared in Example 1; Figure 2 SEM images (at different magnifications) of carbon fiber fabric with polydopamine nanospheres deposited on its surface prepared in Example 1. Figure 3 The image shows a load-temperature comparison of the polydopamine nanospheres in situ blended with phthalonitrile resin composites prepared in Example 1 and Comparative Examples 1-3 during high-temperature CT tensile testing. Detailed Implementation

[0017] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0018] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art may make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0019] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0020] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.

[0021] The phthalonitrile resin used in the following examples is the self-catalytic PN75 (purchased from the Institute of Chemistry, Chinese Academy of Sciences), which contains phthalonitrile groups at the end; the carbon fiber fabric is PAN-based T300 carbon fiber, which is unsizing and has a woven structure.

[0022] Example 1: (1) Pretreatment of carbon fiber fabric The carbon fiber fabric was ultrasonically cleaned for 30 minutes using a mixture of acetone and anhydrous ethanol, and then dried under vacuum for later use.

[0023] (2) In-situ deposition of polydopamine nanospheres At room temperature (25 ± 2°C), 2 g of dopamine hydrochloride was dissolved in a Tris-HCl buffer solution at pH 8.5 to obtain a 2 g / mol dopamine hydrochloride solution. A 100 mm × 100 mm carbon fiber fabric sheet was completely immersed in this system and allowed to stand for 24 hours, during which gentle magnetic stirring was maintained to keep the dissolved oxygen in the solution uniform. Under these conditions, dopamine undergoes self-oxidation and self-polymerization, gradually forming polydopamine nanospheres with a particle size of 100–200 nm, which are then deposited in situ on the surface of the carbon fiber fabric.

[0024] After deposition, the carbon fiber fabric was removed, rinsed three times with deionized water to remove unbound PDA particles, and then vacuum dried at 65°C for 12 hours to obtain a carbon fiber fabric with uniformly loaded polydopamine nanospheres on its surface. SEM images are shown below. Figure 2 As shown.

[0025] (3) Blending and preforming treatment of phthalonitrile resin PN75 phthalic acid resin was dissolved in acetone to prepare an 80wt% solution. After stirring magnetically for 1 hour, the solution was allowed to stand for 12 hours to fully degas.

[0026] Subsequently, the carbon fiber fabric with uniformly loaded polydopamine nanospheres obtained in (2) above was immersed in the resin solution and left to stand at room temperature for 10 hours. After being taken out, it was placed in a 60°C hot air environment for pre-drying for 6 hours to obtain a prepreg sheet with uniform bonding and stable structure.

[0027] (4) Hot pressing curing process The modified phthalocyanine resin sheets are stacked in a specified direction and laid in a mold, and then cured using a five-stage programmable hot pressing process. (1) Stage 1: Heat to 120°C, hold for 90 min, and apply pressure of 0.3 MPa; (2) Stage 2: Heat to 170°C, hold for 110 min, and maintain pressure at 0.3 MPa; (3) Stage 3: Heat to 200°C, hold for 80 min, and apply pressure of 4.0 MPa; (4) Stage 4: Heat to 250°C, hold for 280 min, and maintain pressure at 4.0 MPa; (5) Stage 5: Heat to 315°C, keep warm for 240 min, and complete crosslinking under normal pressure.

[0028] (6) Subsequently, the material was naturally cooled to room temperature in the mold at a rate of 3°C / min, and demolded to obtain a composite material sheet with a thickness of approximately 4 mm and a smooth, defect-free surface, such as... Figure 1 As shown.

[0029] Comparative Example 1: The difference between this comparative example and Example 1 is that: (2) the amount of dopamine hydrochloride used is 0g, and the remaining process steps and parameter settings are the same as in Example 1.

[0030] Comparative Example 2: The difference between this comparative example and Example 1 is that (1) was not performed, and the amount of dopamine hydrochloride used in (2) was 0g. The remaining process steps and parameter settings are the same as in Example 1.

[0031] Comparative Example 3: The difference between this comparative example and Example 1 is that (1) was not performed, and the remaining process steps and parameter settings are the same as in Example 1.

[0032] The specific sample processing schemes of Example 1 and Comparative Examples 1 to 3 are compared in Table 1 below.

[0033] Table 1

[0034] The properties of the composite material sheets prepared in Example 1 and Comparative Examples 1 to 3 were tested: (1) CT sample processing and testing According to GB / T 3356-2014 Test Method for Fracture Toughness of Composite Materials Compact Tension Specimens, each group of composite materials was cut into compact tensile (CT) specimens with a size of 60mm × 60mm and a pre-crack depth of 15mm.

[0035] Tested according to ASTM E399 standard: The test temperatures were set to 25°C, 125°C, 225°C, and 325°C. The tests were conducted using an electronic universal testing machine with a heating chamber. The loading rate was 0.5 mm / min. After holding the machine at the test temperature for 1 hour, the CT compact tensile test was performed, and the maximum load (N) at each temperature point was recorded.

[0036] The test results are shown in Table 2 below. Figure 3 As shown.

[0037] Table 2

[0038] As shown in Table 2 above, at room temperature (25°C), the maximum load of Example 1 reached 2393.93 N, which is 185% of that of Comparative Example 1; at a high temperature of 325°C, Example 1 still maintained a high tensile load of 1775.03 N, which is 162% of that of Comparative Example 2; the comparison between Comparative Example 3 and Example 1 shows that the in-situ blending modification of PDA phthalonitrile also has a good reinforcing effect in the unde-sizing state, but if combined with the de-sizing process, a tighter bond can be formed, further improving the high-temperature load holding capacity; the load of Example 1 decreased by 25.9% from 25°C to 325°C, while that of Comparative Example 1 decreased by 19.5%, but the absolute load-bearing capacity of Example 1 at high temperature is higher, indicating that the structure is more critical for heat-resistant fracture control.

[0039] Example 2: The difference between this embodiment and embodiment 1 is that: (2) the concentration of the hydrochloric acid dopamine solution is 0.5 g / mol, and the other process steps and parameter settings are the same as in embodiment 1.

[0040] Example 3: The difference between this embodiment and embodiment 1 is that: (2) the concentration of the hydrochloric acid dopamine solution is 5.0 g / mol, and the other process steps and parameter settings are the same as in embodiment 1.

[0041] The sample processing schemes of specific Examples 1 to 3 are compared in Table 3 below.

[0042] Table 3

[0043] The polydopamine nanospheres exhibited the following characteristics under different concentration conditions, as determined by SEM analysis: Example 2: Polydopamine nanospheres with a particle size of approximately 50-100 nm and sparsely distributed surface particles; Example 1: Polydopamine nanospheres with a particle size of approximately 100-200 nm and a dense and uniform particle distribution; Example 3: The polydopamine nanospheres have a particle size of approximately 300~1000 nm, and exhibit microsphere aggregation and irregular particle accumulation.

[0044] The high-temperature heat exposure residual properties of the composite material plates prepared in Examples 1-3 were tested. Specifically, the samples were placed in an air atmosphere, kept at 400°C for 1 hour, and then cooled to room temperature before testing. (1) The three-point short beam shear method was used, and the test was conducted according to the ASTM D2344 standard; Testing equipment: Electronic universal testing machine (Instron 5982 or similar equipment), used for high-temperature ILSS testing when equipped with a high-temperature testing furnace, with a loading rate of 1 mm / min.

[0045] (2) Three-point bending strength test (Flexural Strength) shall be conducted in accordance with the ASTM D7264 standard; Test equipment: Electronic universal testing machine (Instron 5982 or similar); loading rate is 2 mm / min.

[0046] The test results are shown in Table 4 below.

[0047] Table 4

[0048] Example 4: The difference between this embodiment and Example 1 is that: (2) is: at room temperature (25 ± 2°C), 2g of dopamine hydrochloride was weighed and dissolved in Tris-HCl buffer solution with pH 8.5 to obtain a dopamine hydrochloride solution with a concentration of 2g / mol. The solution was left to stand for 24h, and slight magnetic stirring was maintained during the process to keep the dissolved oxygen in the solution uniform. Under these conditions, dopamine undergoes self-oxidation and self-polymerization to gradually form polydopamine nanospheres with a particle size of 100~200nm. The nanospheres were collected, dried, and then used for later use. The obtained polydopamine nanospheres, DMF, and phthalic anhydride resin were subjected to solution blending modification. The specific operation process is as follows: Polydopamine nanospheres were added to 100 mL of butanone, heated to 40 °C, and then magnetically stirred at 500 r / min for 30 min while naturally cooling to room temperature to obtain a modified solution. Phthalocyanine resin was heated to 110-120 °C and then added to the modified solution. The mixture was stirred at 800 r / min and then naturally cooled to room temperature to obtain a blended solution. The blended solution was subjected to vacuum distillation at 100 °C and 0.1 MPa to obtain a homogeneous blended modified phthalocyanine resin.

[0049] The remaining process steps and parameter settings are the same as in Example 1.

[0050] The high-temperature heat exposure residual properties of the composite material plates prepared in Examples 1, 4 and Comparative Example 1 are compared, as shown in Table 5 below.

[0051] Table 5

[0052] The above description is only a preferred embodiment of the present invention. Given that those skilled in the art can make appropriate changes and modifications to the above embodiments, the present invention is not limited to the specific embodiments described above, and some modifications and changes to the present invention should also fall within the protection scope of the claims of the present invention.

Claims

1. A method for in-situ blending and modifying phthalocyanine resin with polydopamine nanospheres, characterized in that, include: (1) Clean and dry the carbon fiber fabric for later use; (2) Add dopamine hydrochloride to Tris-HCl buffer to obtain a reaction solution. Immerse the cleaned carbon fiber fabric in the reaction solution at room temperature and let it stand to react, and obtain carbon fiber fabric with polydopamine nanospheres deposited on the surface. (3) The carbon fiber fabric with polydopamine nanospheres deposited on its surface is immersed in phthalic acrylonitrile resin solution, and a segmented heating method is used for immersion pretreatment. Finally, a hot pressing process is used for curing treatment to obtain polydopamine nanosphere in-situ blended modified phthalic acrylonitrile resin.

2. The preparation method according to claim 1, characterized in that, (1) The operation process is as follows: use a mixture of acetone and anhydrous ethanol for ultrasonic cleaning for 30 minutes and dry it under vacuum.

3. The preparation method according to claim 1, characterized in that, (1) The pH value of the Tris-HCl buffer is 8.

5.

4. The preparation method according to claim 1, characterized in that, (2) The concentration of dopamine hydrochloride in the reaction solution is 0.5–5.0 g / mol.

5. The preparation method according to claim 1, characterized in that, (2) The static reaction time is 12-72h.

6. The preparation method according to claim 1, characterized in that, (3) The concentration of phthalonitrile resin solution is 60-80wt%, and the solvent is acetone or / and methyl ethyl ketone; the phthalonitrile resin is a self-catalytic trimer PN resin with active phthalonitrile groups at the end.

7. The preparation method according to claim 1, characterized in that, (3) The pretreatment process of immersion is as follows: keep warm at 50-80°C for 30 minutes, and then raise the temperature to 120-250°C and keep warm for 30 minutes.

8. The preparation method according to claim 1, characterized in that, (3) The curing process is as follows: First, maintain the temperature at 0.2-2 MPa and 100-200°C for 1-4 hours; Then, keep warm at 4-6 MPa and 200-300°C for 1-5 hours; Finally, the material is kept at 4-6 MPa and 300-400°C for 1-5 hours, then cooled to room temperature at a rate of 3-5°C / min before demolding.

9. A polydopamine nanosphere in-situ blended modified phthalocyanine resin composite material prepared by the method according to any one of claims 1 to 8, characterized in that, After being heat-aged at 400°C for 1 hour, its shear strength is not less than 50% of the initial shear strength and its flexural strength is not less than 60% of the initial flexural strength.

10. The application of the polydopamine nanosphere in-situ blended modified phthalocyanine resin composite material according to claim 9, characterized in that, Used in the preparation of heat-resistant structural components.

Citation Information

Patent Citations

  • Modified carbon fiber based on polydopamine film / nanosphere composite structure and preparation method thereof

    CN118345631A

  • Preparation method of Mg (OH) 2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material

    CN119684742A